There goes the bride eaudiobook - Beaton, M. C. (Agatha Raisin Mystery,, 2009)
Bossy, impulsive, yet hopelessly romantic, Agatha is dreading the upcoming marriage of her ex-husband, James Lacey. Although she has set her sights on a handsome and beguiling new Frenchman, she can't quite stop obsessing about James. Her best intentions to move on with her life are put on hold when James's young bride is shot to death just minutes before saying "I do" and Agatha is named the prime suspect. Agatha's sleuthing sidekick Toni stands ready to help find the real killer, but the case proves trickier than ever. Will her name be cleared, or has the outrageous Agatha finally had her last romp?